Daily fluctuations in visual motion discriminability contribute to daily fluctuations in continuous visuomotor performance - Takami, Ayaka; Goya, Ryoma; Aoyama, Chisa; Komiyama, Takaaki; Kawajiri, Toshitaka; Shimegi, Satoshi (Frontiers in Sports and Active Living, 2022)
In ball sports such as table tennis, in which a ball moving at high speed is hit, an athlete's brain needs to process the motion information of the ball, predict the arrival point, and form a motor command to direct the racket there. Therefore, day-to-day fluctuations in visuomotor performance may be ascribed to fluctuations in visual motion discriminability, but it is not clear how the two are related. To examine this point, university table tennis players performed a motion direction discrimination (MDD) task and continuous visuomotor (CVM) task over 10 days as an estimation of visual motion discriminability and visuomotor performance, respectively. In the MDD task, using a joystick, participants distinguished the direction of a global coherent motion of target dots moving in the same direction on a PC monitor from innumerable dots moving in random directions. In the CVM task, participants hit sequential targets moving fast from right to left on the PC monitor by operating the cursor on the left side of the monitor up and down using the prehensile force of their thumb and index finger. The scores in the MDD and CVM tasks fluctuated day by day and showed a significant and moderate correlation between the MDD task score for the visual field in which the participants captured the target in the CVM task and the CVM task score. This correlation was confirmed even with the target moving from left to right. The fluctuations in the onset latency and the endpoint position of the cursor movement approaching the target were correlated with those of the visual motion discriminability, suggesting the contribution of motion vision to the speed and accuracy of the visuomotor performance. Moreover, these relationships were prominent in veteran players. For table tennis athletes, especially experienced players, fluctuations in the visual motion discrimination performance in a visual field specific for capturing a ball may be responsible for the fluctuations in continuous visuomotor (striking) performance.